Initial experience with the 3.3 Fr Mongoose® pigtail catheter for aortic angiography during patent ductus arteriosus closure in small patients - Zachary Hena; Nicole J Sutton; Gregory J Gates; Benjamin H Taragin; Robert H Pass (Wolters Kluwer Medknow Publications, 2017)
Background: Smaller femoral arterial sheaths may be associated with fewer vascular complications. The 3.3 Fr Mongoose® Pediavascular pigtail catheter is a catheter that allows higher flow rates, potentially resulting in improved angiographic quality. We reviewed our experience with this small catheter during patent ductus arteriosus (PDA) closure. Materials and Methods: Review of patients ≤20 kg in whom the Mongoose® catheter was used during PDA closure from 12/13 to 4/15. Angiographic efficacy and procedural details were compared to ten 4 Fr catheter cases. Comparisons were performed using Mann-Whitney U-test; P < 0.05 was statistically significant. Results: Twelve (9 female) patients were catheterized with a 3.3 Fr Mongoose®. Median weight 10.5 kg (range 6.4-18.2), height 81 cm (range 37-111), and body surface area (BSA) 0.47 m2 (range 0.33-0.75) were similar to ten patients (3 females) in the 4 Fr control group (P = NS); median weight 9.9 kg (range 6-16.8), height 80 cm (range 64-102), and BSA 0.46 m2 (range 0.31-0.74). Angiographic quality was subjectively adequate with both with no difference in the median pixel density between the two techniques (3.3 Fr: 76.7 [range 33.5-90] and 4 Fr: [70; 38-102]; P = NS). Contrast used was similar between the groups (3.3 Fr: median 4.2 ml/kg and 4 Fr: 4.9 ml/kg; P = NS). Median radiation dose was similar in the two groups (3.3 Fr: 28.1 mGy [range 17.2-38] and 4 Fr: 38 mGy [range 20.4-58.5]; P = NS). All ducts were closed at latest follow-up ( P = NS). No complications were encountered. Conclusions: The 3.3 Fr Mongoose® allowed similar angiography to the 4 Fr pigtail catheter, allowing safe and effective transcatheter PDA closure in small children.